2005
DOI: 10.1007/s00127-005-0905-2
|View full text |Cite
|
Sign up to set email alerts
|

Duration of untreated psychotic illness

Abstract: Both poor diffuse social support and a low socio-economic status seem to be relevant factors of a prolonged duration of untreated psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our study therefore supports individual- and familial-based initiatives to reduce the duration of untreated psychosis in the community, such as the provision of early intervention in psychosis services, which aim to improve the long-term outcomes of severe mental illness by providing early treatment and care to people with psychosis (Department of Health, 2001; Lester et al, 2009) It is, however, noteworthy that important clinical and social inequalities in DUP (Morgan et al, 2006a), and pathways to care (Morgan et al, 2005a, 2005b), remain for some groups. There is also some evidence that poor social support may lengthen the duration of untreated psychosis (Peralta et al, 2005), which overlaps with our previous finding that family involvement is also important in reducing DUP (Morgan et al, 2006a). One previous study has shown that DUP can be reduced for individuals when early detection services exist in their communities (Melle et al, 2004), suggesting that while the determinants of DUP may not operate directly at the neighbourhood level, it does provide a suitable target for intervention strategies to reduce DUP.…”
Section: Resultssupporting
confidence: 86%
“…Our study therefore supports individual- and familial-based initiatives to reduce the duration of untreated psychosis in the community, such as the provision of early intervention in psychosis services, which aim to improve the long-term outcomes of severe mental illness by providing early treatment and care to people with psychosis (Department of Health, 2001; Lester et al, 2009) It is, however, noteworthy that important clinical and social inequalities in DUP (Morgan et al, 2006a), and pathways to care (Morgan et al, 2005a, 2005b), remain for some groups. There is also some evidence that poor social support may lengthen the duration of untreated psychosis (Peralta et al, 2005), which overlaps with our previous finding that family involvement is also important in reducing DUP (Morgan et al, 2006a). One previous study has shown that DUP can be reduced for individuals when early detection services exist in their communities (Melle et al, 2004), suggesting that while the determinants of DUP may not operate directly at the neighbourhood level, it does provide a suitable target for intervention strategies to reduce DUP.…”
Section: Resultssupporting
confidence: 86%
“…The necessity of preventive treatment in bipolar disorder is indisputable to prevent relapses, reduce the risk of suicide and prevent psychosocial consequences of the episodes [23]; furthermore, delayed institution of preventive treatment is related to poor disease course in bipolar disorder [24]. Conversely, the importance of the time lag between the first onset of disorder symptoms and the initiation of treatment in psychotic disorders has been studied extensively; these studies reported that weak social support is related to delayed treatment in the first-episode psychotic patients [25,26]. In a study examining the effect of time before receiving the diagnosis of bipolar disorder on the clinical outcomes, McCraw et al [27] reported a relationship between the perceived social support and the time until diagnosis in bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…While it was possible to obtain data on a range of demographic and diagnostic variables, it was not possible to obtain detailed diagnostic and symptom data using clinical rating scales such as the SCAN[ 36 ] or YMRS[ 37 ]. Previous studies have indicated that factors such as employment status[ 38 ], social support[ 39 ], deliberate self-harm[ 40 ] and the clinical experience of clinicians who first assess patients may play a role in determining delays to diagnosis and treatment. Although it was possible to analyse data on age, gender, ethnicity and marital status in our study, it was not possible to obtain data on other factors from routinely recorded electronic health records.…”
Section: Discussionmentioning
confidence: 99%